2005
DOI: 10.3748/wjg.v11.i19.2869
|View full text |Cite
|
Sign up to set email alerts
|

Presence and integration of HBV DNA in mouse oocytes

Abstract: AIM: Hepatitis B is a worldwide public health problem. To explore the feasibility of hepatitis B virus (HBV) vertical transmission via oocytes, the presence and integration of HBV DNA in mouse oocytes were studied. METHODS:Genomic DNA was isolated and metaphases were prepared, respectively from mouse oocytes cocultured with pBR322-HBV DNA plasmids. PCR, Southern blot, dot hybridization and fluorescence in situ hybridization (FISH) were performed to explore the existence and integration of HBV DNA in oocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
(15 reference statements)
1
13
0
4
Order By: Relevance
“…The research on hepatitis B virus has shown that the viral DNA can pass through the zona and oolemma and enter into oocytes by sperm [30], [31]. Furthermore, it was also reported that the virus can be absorbed into the fish sperm and vertically transmitted [32].…”
Section: Discussionmentioning
confidence: 99%
“…The research on hepatitis B virus has shown that the viral DNA can pass through the zona and oolemma and enter into oocytes by sperm [30], [31]. Furthermore, it was also reported that the virus can be absorbed into the fish sperm and vertically transmitted [32].…”
Section: Discussionmentioning
confidence: 99%
“…El HBV se ha encontrado en sangre, saliva, leche materna, secreciones vaginales y semen, siendo transmitido principalmente por vía parenteral, sexual y perinatal (Zea-Mazo et al). Se ha determinado secuencias de DNA de HBV en cromosomas de espermatozoides, donde el virus posiblemente ha atravesado la barrera hematotesticular e infectado a la línea germinal masculina y también en oocitos de ratón, lo cual es de gran importancia debido a la posibilidad que el feto pueda adquirir la infección a través de la madre (Huang et al, 2005). En humanos, el virus es detectable en muestras de semen de hombres con hepatitis B aguda así como en el semen de hombres con hepatitis crónica (Leruez-Ville et al, 2005a).…”
Section: Virus Epstein-barr (Ebv) El Virus De Epstein-barr (Ebv)unclassified
“…Approximately one third of HBV infections occur via perinatal transmission [28], and perinatal transmission is the most important vertical transmission route of chronic hepatitis B infection. Perinatal transmission of HBV is mediated via three main modes: 1) Intrauterine transmission; 2) Intrapartum or labour transmission; and 3) Postnatal transmission.…”
Section: Perinatal Transmissionmentioning
confidence: 99%